Prolonged electrical stimulation causes no damage to sacral nerve roots in rabbits - Yan, Peng (Medknow Publications & Media Pvt Ltd, 2014)
Previous studies have shown that, anode block electrical stimulation of the sacral nerve root can produce physiological urination and reconstruct urinary bladder function in rabbits. However, whether long-term anode block electrical stimulation causes damage to the sacral nerve root remains unclear, and needs further investigation. In this study, a complete spinal cord injury model was established in New Zealand white rabbits through T(9–10) segment transection. Rabbits were given continuous electrical stimulation for a short period and then chronic stimulation for a longer period. Results showed that compared with normal rabbits, the structure of nerve cells in the anterior sacral nerve roots was unchanged in spinal cord injury rabbits after electrical stimulation. There was no significant difference in the expression of apoptosis-related proteins such as Bax, Caspase-3, and Bcl-2. Experimental findings indicate that neurons in the rabbit sacral nerve roots tolerate electrical stimulation, even after long-term anode block electrical stimulation.